Relationships between anaemia and parasitic infections in adolescent girls of Bangladesh (Bangladesh Journal of Zoology, 2015)
A total of 1570 adolescent girls (aged 10-19 years) of rural, urban and slum areas in and around Dhaka city were investigated to determine the association of anaemia with parasitic infection. About one third (33.50%) of the adolescent girls were found to be infected with one or more protozoans (Entamoeba histolytica, Giardia lamblia) and helminths (Ascaris lumbricoides, Trichuris trichura, Strongyloieds stercoralis, hookworms). Anaemia (32.22%) was reported among the adolescent girls and 39.52% anaemic girls were infected with intestinal parasites against the 30.63% non anaemic cases. Anaemia was significantly associated with parasitic infestation (?2 =11.76, p